Artificial Bee Colony Algorithm for Economic Load Dispatch Problem - Hardiansyah Hardiansyah (Institute of Advanced Engineering and Science, 2013)
In practical cases, the fuel cost of generators can be represented as a quadratic function of real power generation and satisfied constraints for minimizing of fuel cost. Artificial Bee Colony (ABC) algorithm is used for the optimization of active power dispatch of generating units. The proposed method is able to determine, the output power generation for all of the power generation units, so that the total cost is minimized. Simulation and analysis of economic load dispatch using Artificial Bee Colony (ABC) algorithm is proposed. The obtained results are compared with the conventional method, genetic algorithm (GA) and shows that the ABC algorithm approach is more feasible and efficient for finding minimum cost.DOI: http://dx.doi.org/10.11591/ij-ai.v2i2.1613